(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Flat foot deformity is a prevalent musculoskeletal condition that affects lower limb biomechanics and may contribute to altered posture and spinal alignment. Despite substantial research on its association with lower limb pain, limited evidence exists regarding its link to spinal disorders, particularly neck and low back pain. Objective: To determine the prevalence and association of neck and low back pain in individuals with flat foot deformity compared to those with normal foot posture. Methodology: A descriptive cross-sectional study was conducted from January to May 2025 at a tertiary physiotherapy clinic in Peshawar, Pakistan. A total of 180 participants aged 18 to 45 years were enrolled using non-probability purposive sampling. Participants were categorized into two groups based on the Foot Posture Index (FPI-6): flat foot (n = 90) and normal foot posture (n = 90). Neck and back pain severity were assessed using the Neck Disability Index (NDI) and Oswestry Disability Index (ODI), respectively. Pain intensity and interference with daily activities were also recorded. Data were analyzed using SPSS v25, employing descriptive statistics, chi-square test, and independent t-test. A p-value < 0.05 was considered statistically significant. Results: The flat foot group showed a higher prevalence of neck pain (67.8%) and low back pain (77.7%) compared to the normal foot group (31.1% and 37.7%, respectively). A significant proportion (60%) of flat-footed participants reported both neck and back pain concurrently, compared to 23.3% in the normal group (p < 0.05). The mean NDI and ODI scores were significantly greater in the flat foot group, indicating moderate disability levels. Conclusion: Flat foot deformity is significantly associated with increased prevalence and severity of neck and low back pain. These findings emphasize the importance of including foot posture assessment in routine evaluation of patients presenting with spinal pain.